Zapora centralne vene mrežnice na edinem funkcionalnem očesu - Jaki Mekjavić, Polona (Zdravniški vestnik, 2012)
Aim: Presentation of a group of a seven patients, who all developed central retinal vein occlusion (CRVO) in the only functional eye, and were treated with bevacizumab (AvastinŽ). Methods: The diagnosis was established on the basis of a significant clinical picture. Prior to the treatment, we determinedvisual acuity (ETDRS) and performed optic coherence tomography (OCT). All patients received three serial injections of bevacizumab (AvastinŽ)at monthly intervals. We evaluated the effect of the treatment everymonth, over a period of one year. In the case of persistent oedema in themacula, bevacizumab was injected again. Results: The visual acuity improvedin all patients. A significant morphological change was observed: a reduction in the thickness of the central retina and the volume of the retina,as determined by OCT. Conclusions: The treatment of central retinal vein occlusion with bevacizumab (AvastinŽ) in patients with only one functional eye resulted in a good morphological and functional outcome. This may be partly due to the fact that patients with only one functional eye are much more sensitive to changes in visual acuity in that eye, and are much morelikely to seek treatment earlier than would such patients with both functional eyes. Also, patients with one functional eye are more motivated to diligently monitor their cardiovascular risk factors than those with both functional eyes.
Keywords: bevacizumab; mrežnica; zapora centralne vene